Days of Youth - Hughes, Ed (The Ozu Collection, 2011)
As the film opens, a gregarious loafer named Watanabe (Ichiro Yuki) turns away a young man who has inquired about a sign on the window for a room for rent, explaining that he had just rented the room earlier that day. Moments later, an attractive young woman inquires about the same room and, attempting to get into her good graces, Watanabe remarks that he is in the process of vacating and that the room is available. With nowhere to go, he moves into the apartment of his meek, bookish friend Yamamoto (Tatsuo Saito) who, unbeknownst to him, is enamored with the same young woman. After completing their final examinations, the two friends decide to bide time waiting for their final grades by competing for the affection of the young woman at a ski resort, resulting in a series of misadventures for the novice skier Yamamoto. The earliest extant film by Ozu, "Days of Youth" is a whimsical, amusing, and entertaining fusion of physical and situational comedy. Most noteworthy in the film is the absence of Ozu's familiar 'pillow' shots that are functionally replaced by the use a bookend, long panning panorama shots of the city to convey placement and scenario. [www.filmref.com]